COST-EFFECTIVENESS STRATEGY FOR DEVELOPING CLEAN WATER SERVICE IN SUKAMAKMUR VILLAGE, BOGOR - Sasongko, Hendro; Alipudin, Asep; Herlisnawati, Dessy (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2024)
ABSTRACT This study aims to assess the benefits of PLT-EM in the cost-effectiveness strategy scheme for developing a drinking water supply system. The research approach is descriptive quantitative using incremental analysis methods, water consumption and discharge calculation formulations, and financial analysis models. The data used are secondary in the form of BUMdesa production and financial reports. Based on the assessment results, using PLT-EM can develop a drinking water supply system by increasing the volume of water and consistency of water distribution to the community. The cost-effectiveness strategy can be implemented through incremental analysis between investment and operational costs with revenue from water sales before and after using PLT-EM by considering the addition of water production capacity and the potential for expanding service coverage to the community. ABSTRAK Penelitian ini bertujuan untuk mengkaji manfaat PLT-EM dalam skema strategi efektivitas biaya dalam rangka pengembangan sistem penyediaan air minum. Pendekatan penelitian yang digunakan adalah deskriptif kuantitatif dengan menggunakan metode analisis inkremental, formulasi perhitungan konsumsi dan debit air, serta model analisis finansial. Data yang digunakan adalah data sekunder berupa produksi BUMdesa dan laporan keuangan. Berdasarkan hasil pengkajian, pemanfaatan PLT-EM dapat mengembangkan sistem penyediaan air minum dengan meningkatkan volume air dan konsistensi distribusi air kepada masyarakat. Strategi efektivitas biaya dapat diterapkan melalui analisis inkremental antara biaya investasi dan biaya operasional dengan pendapatan dari penjualan air sebelum dan sesudah pemanfaatan PLT-EM, dengan mempertimbangkan penambahan kapasitas produksi air dan potensi perluasan jangkauan layanan kepada masyarakat.